2022
DOI: 10.1002/pat.5916
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of crystallization kinetics of polyoxymethylene in processing conditions

Abstract: In this work, a very wide set of quiescent isothermal and non‐isothermal calorimetric experiments are carried out in order to analyze POM crystallization kinetics also under cooling rates comparable to those experienced by the polymer during processing. To investigate the effect of flow on the POM crystallization behavior, also some Linkam shearing tests are conducted. An enhancement of the POM crystallization process is observed under flow. A Kolmogoroff–Avrami–Evans (KAE) model for quiescent crystallization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Figure shows the onset temperatures of crystallization as a function of the cooling rate. The decrease of the crystallization temperature ( T c ) with increasing cooling rate is minor up to around 800 K s –1 , while it becomes more distinct on cooling at rates higher than 1000 K s –1 , being consistent with data in the literature. , …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Figure shows the onset temperatures of crystallization as a function of the cooling rate. The decrease of the crystallization temperature ( T c ) with increasing cooling rate is minor up to around 800 K s –1 , while it becomes more distinct on cooling at rates higher than 1000 K s –1 , being consistent with data in the literature. , …”
Section: Resultssupporting
confidence: 87%
“…55−57 The chemical repeat unit of POM is −[−O−CH 2 −]−, and the linear and flexible chain structure facilitates rapid crystallization. 58 The equilibrium melting temperature and glasstransition temperature are around 200 and −85 °C, respectively, 59−62 and crystallization of the quiescent melt typically yields folded chain lamellae and spherulites. 61,62 The present study is an attempt to provide on one side fundamental and quantitative data about the effects of cooling rate and shear rate on the crystallization behavior of POM, using conventional analysis tools such as calorimetry and rheology.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that, due to differences in entropy, these various conformations of molecular chains showcase different crystallization temperature upon cooling. Additionally, the cooling rate is a significant factor affecting the non-isothermal crystallization behavior of semi-crystalline polymers, profoundly influencing the nucleation and subsequent crystal growth behaviors [47][48][49][50][51][52]. Therefore, it is imperative to focus on the influence of varying cooling rates on crystallization temperature of PPS when PPS exhibits SN behaviors.…”
Section: Effect Of the Cooling Rate In The Second Thermal Cycle On Th...mentioning
confidence: 99%
“…6, it is found that the molten structure formed by laser ablation of POM gradually decreases with increasing scanning speed, and although the decrease of melt-like structure is beneficial to the macroscopic morphology, it has a negative effect on the surface roughness. As a common polymer, the crystallization properties of POM materials are positively correlated with heat treatment time and temperature in a specific temperature range [30]. As the scanning speed increases, the time for the texture to be radiated by the laser becomes shorter, the conduction and diffusion processes of energy on the material are shortened, the heat treatment time is shorter, and the crystallinity of the bottom surface of the texture is poor, which leads to the rise of its overall surface roughness.…”
Section: Influence Of Laser Power On Texturementioning
confidence: 99%